(untitled) (Global Journal of Human-Social Science, 2016)
The history of the concept and identification of Learning Disabilities (LD) has important stages of development which should be considered by the researchers of this field. This development includes different thoughts and experiments which are still controversial until recently. This paper discusses this development and divides it into four periods which consider different factors of each period such as: the location, scholars and critical perspectives and practices. Discussion about the impact of the history on the current period is provided.